Immunochromatographic colloidal carbon-based assay for detection of methiocarb in surface water - Blazková, Martina; Micková-Holubová, Barbora; Rauch, Pavel; Fukal, Ladislav (Biosensors & bioelectronics, 2009)
A simple and rapid immunochromatographic assay for a sensitive and inexpensive monitoring of methiocarb in surface water was developed using a binding inhibition format on a membrane strip. In the assay, detection reagent consisted of anti-methiocarb antibody and colloidal carbon-labelled secondary antibody. Methiocarb-ovalbumin conjugate was immobilized in a test line of the strip as a capture reagent. Colour intensity of the test line in methiocarb-positive assay was visually distinguishable from that of negative sample within 10min. The optimized semi-quantitative method provided a visual detection limit of 0.5ngmL(-1). Cross-reactions with other carbamate pesticides were not found (<1%). Only a negligible matrix effect of surface water was recognized. In parallel analyses of spiked water samples, the assay results were in a good agreement with those of ELISA. The stability test indicated the strips could be used at least 2 months without change in performance. All characteristics of the visually evaluated assay mentioned above were verified by instrumental quantification of colour intensity in test lines. The developed immunochromatographic assay offers potential as a useful on-site screening tool for environmental analysis.
Keywords: chromatografie; Carbon; Colloids; imunoanalýza; methiokarb; Water Pollutants, Chemical; biosenzitivní techniky; Biosensing Techniques; Chromatography; Water; koloidy; Methiocarb; uhlík; chemické látky znečišťující vodu; Immunoassay; voda